2011
DOI: 10.1186/1687-4722-2011-11
|View full text |Cite
|
Sign up to set email alerts
|

Semantic structures of timbre emerging from social and acoustic descriptions of music

Abstract: The perceptual attributes of timbre have inspired a considerable amount of multidisciplinary research, but because of the complexity of the phenomena, the approach has traditionally been confined to laboratory conditions, much to the detriment of its ecological validity. In this study, we present a purely bottom-up approach for mapping the concepts that emerge from sound qualities. A social media (http://www.last.fm) is used to obtain a wide sample of verbal descriptions of music (in the form of tags) that go … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…In an interlanguage comparative study of English and Greek speakers, for instance, Reiss (2014, 2015) found that timbre is commonly conceptualized in terms of luminance (''bright''), texture (''smooth''), and mass (''dense''). Similar findings have appeared in crossmodal studies in music perception (Eitan & Rothschild, 2010), written discourse of orchestration (Kendall & Carterette, 1993a;Wallmark, 2019b), social tagging in online music streaming services (Ferrer & Eerola, 2011), and interviews with professional musicians (Reymore & Huron, 2020) and studio engineers (Porcello, 2004). However, the presence of semantic crossmodal relations in the written and spoken discourse of timbre provides only partial and circumstantial evidence for genuine crossmodal interactions; labeling a tone ''bright'' might indicate, although it does not necessarily indicate, any mechanistic link between the processing of auditory and visual brightness.…”
Section: Timbre and Crossmodal Perceptionsupporting
confidence: 66%
“…In an interlanguage comparative study of English and Greek speakers, for instance, Reiss (2014, 2015) found that timbre is commonly conceptualized in terms of luminance (''bright''), texture (''smooth''), and mass (''dense''). Similar findings have appeared in crossmodal studies in music perception (Eitan & Rothschild, 2010), written discourse of orchestration (Kendall & Carterette, 1993a;Wallmark, 2019b), social tagging in online music streaming services (Ferrer & Eerola, 2011), and interviews with professional musicians (Reymore & Huron, 2020) and studio engineers (Porcello, 2004). However, the presence of semantic crossmodal relations in the written and spoken discourse of timbre provides only partial and circumstantial evidence for genuine crossmodal interactions; labeling a tone ''bright'' might indicate, although it does not necessarily indicate, any mechanistic link between the processing of auditory and visual brightness.…”
Section: Timbre and Crossmodal Perceptionsupporting
confidence: 66%
“…Methodologically, this study demonstrated the novel analytical potential of using natural language data, as acquired through large text corpora, to explore issues in timbre perception and cognition typically approached using methods from experimental psychology (cf. Ferrer & Eerola, 2011;Kendall & Carterette, 1993). In showing certain linguistic consistencies in timbre description that complement the experimental literature, these findings could have implications for the development of music information retrieval systems (Leman, 2007) and computer music interfaces (Gounaropoulos & Johnson, 2006).…”
Section: Resultsmentioning
confidence: 54%
“…Other recent studies have leveraged the Internet to infer common semantic structures for timbre. Analyzing a large dataset of descriptive terms (or, "social tags") for music, Ferrer and Eerola (2011) used latent semantic analysis to assess trends in timbre description across a broad range of musical genres. They found 19 semantic clusters reducing to five latent factors (energetic, intimate, classical, mellow, and cheerful), which cut across most genres and could be explained by a relatively small set of acoustic features.…”
Section: Text Corpus Studies and Timbrementioning
confidence: 99%
“…In subjective descriptions, listeners rate the attributes that describe their subjective experiences with respect to emotions, liking or interest (Beveridge & Knox, 2009; Juslin & Laukka, 2003; Rentfrow et al, 2011; Rentfrow et al, 2012; Zentner et al, 2008). This method is not only common in research, but also in real-life settings, where individuals use social tags, short semantic labels, to describe music to others (Eerola & Ferrer, 2009; Ferrer & Eerola, 2011; Ferrer, Eerola, & Vuoskoski, 2012). In objective description, the inner, sonic features of music are directly extracted from audio files using Music Information Retrieval techniques (MIR; Dunn, de Ruyter & Bouwhuis, 2011; Dunn, Jurgen, Jaap, & Aroyo, 2009; Eerola, Lartillot, & Toiviainen, 2009; Lamere, 2008; MacDorman, Ough, & Ho, 2007).…”
Section: Description Of Musical Attributes As Intrinsic Determinants mentioning
confidence: 99%